Analysis of Communication Effectiveness in Motivating Employees (Case Study at PT AMG Plastik Industri) - Supriatna, Asep; Mahardhika, Bani; Akbar, Nurul; Wahyudi, Oki; Asih, Putri Sekar; Razali, Geofakta (Indonesian Journal of Entrepreneurship and Startups, 2023)
PT Industri Plastik AMG (AMG Plastic) has departments of the company whose job is to carry out its workflow. In the task of preparing HR needs so that they have the qualifications in accordance with what the company is looking for, it cannot be separated from the role of employees in the Human Relations Division (HRD). The employees in this division are an important part, in which to increase the motivation of these employees must be fully supported by the role of the division head at PT Industri Plastik AMG (AMG Plastic) in creating a good internal company relationship and the relationship between superiors and subordinates. The research method approach used in this study is a qualitative research method by adapting theories related to organizational communication and employee motivation theories through observation, question and answer and retrieval of documentation related to how communication activities are carried out by superiors towards employees to provide constructive motivation to improve performance and work commitment at PT Industri Plastik AMG (AMG Plastic)